(Mass Spectrometric) Non Target Screening-Techniques and Strategies - Letzel, Thomas (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
(Mass spectrometric) non-target screening is a preferably comprehensive and untargeted (predominantly organic molecules detecting) approach combining (robust) analytical measurements with adapted data evaluation concepts, systematic compound identification workflows, and statistical data interpretation. It is well suitable for the identification of new, unexpected and/or unknown organic compounds as well as monitoring 'molecular fingerprints' and profiling 'process-relevant' molecules via statistical methods. In recent years, 14 articles in various disciplines were published and presented in this Special Issue, whereby it contains 4 peer-reviewed review articles and 10 peer-reviewed research articles dealing with non-target screening strategies and solutions.